2022
DOI: 10.1001/jamanetworkopen.2022.0444
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Representation of Low- and Middle-Income Countries in Randomized Clinical Trials for COVID-19

Abstract: regarding trial sponsor, recruitment by country and other trial characteristics were extracted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“… 60 This trend continued in COVID-19-related randomized controlled trials (vaccine and non-vaccine) with 84% of participants being recruited from high-income countries. 61 Our study found that while many vaccines in Phase 4 during 2021 employed a global research strategy with clinical trials in more than five countries (75%), the majority of Phase 2/3 (0%) and Phase 3 (12%) vaccines did not.…”
Section: Resultsmentioning
confidence: 62%
“… 60 This trend continued in COVID-19-related randomized controlled trials (vaccine and non-vaccine) with 84% of participants being recruited from high-income countries. 61 Our study found that while many vaccines in Phase 4 during 2021 employed a global research strategy with clinical trials in more than five countries (75%), the majority of Phase 2/3 (0%) and Phase 3 (12%) vaccines did not.…”
Section: Resultsmentioning
confidence: 62%
“…26,27 Strengths of this report include selection of a vitamin C regimen based on promising initial evaluations, 19,28 excellent treatment adherence and follow-up, and enhanced generalizability based on enrollment in broad geographic areas. 29…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, larger trials that provide evidence of the efficacy of nafamostat mesylate in the treatment of COVID-19 are urgently needed. However, the unascertained viral evolution, the impediments procuring nafamostat for study given the limited number of manufacturers around the world, the logistics of administering a 24-h continuous IV infusion in COVID-19 patients as well as the broader organisational challenges with researching during a global pandemic [ 48 , 49 ] ensure that performing such larger trials for nafamostat is difficult.…”
Section: Discussionmentioning
confidence: 99%